The Impact of Armed Conflict on Services and Outcomes Related to Maternal and Reproductive Health in North Wollo, Amhara, Ethiopia: A Qualitative Study - Kodo TK; Kidie AA; Merecho TH; Tiruneh MG; Yayeh BM; Getaneh BA; Demesie AM; Wendimagegn ZS (Dove Medical Press, 2024)
Tsion Kokeb Kodo,1 Atitegeb Abera Kidie,1 Tilahun Hailu Merecho,1 Misganaw Guadie Tiruneh,2 Berihun Mulu Yayeh,1 Betel Assalfew Getaneh,3 Alexander Mersha Demesie,4 Zeru Seyoum Wendimagegn5 1Department of Public Health, College of Health Science, Woldia University, Woldia, Ethiopia; 2Department of Health Systems and Policy, Institute of Public Health, College Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Midwifery, College of Health Science, Woldia University, Woldia, Ethiopia; 4Department of Pharmacy, College of health Science, Woldia University, Woldia, Ethiopia; 5School of Medicine, College of health Science, Woldia University, Woldia, EthiopiaCorrespondence: Tsion Kokeb Kodo, University of Woldia, P. O. Box 400, Woldia, Ethiopia, Tel +251929364285, Fax +0335400672, Email tsionkokeb@gmail.comIntroduction: Armed conflict is a public health problem that poses a serious challenge to the health system. Maternal and reproductive health is among the most affected areas. Maternal death rates were highest in conflict-affected countries. Sexual violence and rape are commonplaces, which contributes to the rise in the number of unwanted pregnancies. Reliable data related to the health of mothers and reproduction is required to inform public health policies. Therefore, this study aimed to assess the impact of armed conflict on services and outcomes related to maternal and reproductive health.Objective: To explore the impact of armed conflict on services and outcomes related to maternal and reproductive health in North Wollo, Amhara, and Ethiopia by 2022.Methods: This study used an institutional and community-based exploratory design. Six focus group discussions and 44 in-depth interviews were conducted with healthcare professionals, administrators, women, and Non Governmental Organization workers. Each item was recorded in audio, verbatim transcription was made and converted into English. By using OpenCode version 4.03 thematic analyses was performed.Results: Three overarching themes were identified. The first theme was the inadequate standards of maternal and reproductive health services. This includes the breakdown of infrastructure, shortages of medicines and medical supplies, and the lack of sterility of available limited materials and procedures. The second theme was poor maternal and reproductive health status. It includes poor pregnancy, delivery, reproductive and fertility-related health outcomes. The last theme was the limited access to maternal and reproductive services.Conclusion: Armed conflicts have enormous effects on services and results related to the health of mothers and reproductive processes. Addressing these effects is essential for designing and implementing public health measures to improve services related to the health of mothers and the reproductive system.Keywords: armed conflict, effect, maternal and reproductive health, qualitative study